Методи і прилади контролю викидів автозаправних станцій - Івасенко, В. М.; Приміський, В. П. (НТУ "ХПІ", 2014)
Проаналізовано особливості впливу роботи автозаправних станцій (АЗС) на довкілля, характеристики джерел утворення і викидів від АЗС. Розглянуті методи газового аналізу і схеми побудови автоматичних газоаналізаторів, що використовуються для контролю стану забруднення атмосфери на АЗС. Розглянуті вдосконалені схеми термокаталітичного, інфрачервоного, полум’яно-іонізаційного газоаналізаторів.

It was analyzed specific influence of petrol stations operating on environment, features of creation's sources and emissions of petrol stations. It was taken a look on methods of gas analysis and schemes of building of automatic gas analyzers, which are used at petrol stations for atmosphere’s pollution control.It was taken a look on a improved scheme of thermo- catalysis, infrared, flaming ionization gas analyzers. Describe a improved scheme of measuring the concentration evaporation of petrol stations in the air by stabilization of the zero indicators gas analyzer of different methods of gas analysis at continuous work. Thus, we achieve zero scale installation without special analyzer of verification gas and reduce additive measurement error and improve the measurement accuracy.
Methods and emission control devices petrol stations
Keywords: маса; термокаталітичний; газоаналізатор; полум'яно – іонізаційний; інфрачервоний; випаровування; паливо; volume; emission; petrol station; flaming ionization; infrared; vaporization